Clinical Characteristics and Treatment of Intra-abdominal Aggressive Fibromatosis: A Retrospective Study of 16 Patients - Xiao, Jianchun; Mao, Jinzhu; Li, Binglu (Frontiers in Medicine, 2020)
Background: This study aimed to investigate the clinical characteristics and treatment methods for intra-abdominal aggressive fibromatosis. Methods: We reviewed the clinical data from 16 patients who were diagnosed with intra-abdominal aggressive fibromatosis and were admitted to Peking Union Medical College Hospital between March 1983 and September 2018. Results: Among the 16 patients, 11 patients presented with a hard smooth abdominal mass with clear borders and a diameter of 4.3–25.0 cm. Six patients had a history of abdominal surgery and 3 patients had a history of familial adenomatous polyposis. Computed tomography imaging revealed a slightly dense mass with mild-to-moderate enhancement. Of all the 16 patients, 11 patients underwent surgical treatment and no recurrence occurred in 10 case after complete resection while recurrence occurred in 1 case after partial resection. Two patients underwent surveillance and 3 patients received cytotoxic drugs treatment, and no disease progression was observed via imaging during their follow-up. Conclusions: Intra-abdominal aggressive fibromatosis is histologically benign tumor with high local recurrence rate. Surgery is an effective treatment and complete resection is essential in reducing the local recurrence rate.